Dietary protein intake in school-age children and detailed measures of body composition: the Generation R Study. Issue 10 (October 2018) - Jen, Vincent; Karagounis, Leonidas; Jaddoe, Vincent; Franco, Oscar; Voortman, Trudy
Abstract Background A high-protein diet in infancy increases the risk of obesity, but the effects of dietary protein intake in mid-childhood on body composition are unclear. Therefore, we studied associations of protein intake (total, animal and plant-sourced) at 8 years of age with anthropometric measures and body composition up to age 10 years. Methods We included 3991 children of the Generation R Study, a prospective cohort in the Netherlands. Dietary protein intake was assessed at 8 years of age using a food-frequency questionnaire and is expressed in energy percentage (E%). Anthropometric measures and body composition (using dual-energy X-ray absorptiometry (DXA)) were assessed at 6 years and during follow-up at 10 years. We calculated body mass index (BMI), fat mass index (FMI), and fat-free mass index (FFMI). All outcomes were sex- and age-standardized and overweight (yes/no) was derived from BMI-SDS. We examined associations of protein intake at 8 years with the combined risk of overweight and obesity, and body composition at 10 years using multivariable logistic and linear regression models. These analyses were adjusted for outcomes at 6 years and protein intake in early life. Results In multivariable-adjusted models, a 5E% higher protein intake at 8 years was associated with a higher combined risk of overweight and obesity up to 10 years (odds ratio (OR) 1.51, 95% confidence interval (CI): 1.22, 1.86), independent of whether it replaced carbohydrates or fat. However, this was mainly explained by an association of protein intake with a higher FFMI (0.07 standard deviation scores (SDS) per 5E%, 95% CI: 0.02, 0.11), not FMI. Both plant and animal were associated with a higher FFMI, but the association was stronger for protein from plant sources. For FMI, our findings also suggest trends of higher plant protein intake with lower FMI, and higher animal protein intake with higher FMI. Following this, a higher plant protein intake at the expense of animal protein was associated with a lower FMI (−0.08 SDS per 5E%, 95% CI: −0.15, −0.01). Conclusions We observed that a higher protein intake in mid-childhood is associated with a higher fat-free mass. Our findings also suggest that protein from plant sources seems to be beneficial for body composition in school-age children.